2012
DOI: 10.1007/s00217-012-1764-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grape pre-drying and static pomace contact on physicochemical properties and sensory acceptance of Brazilian (Bordô and Isabel) red wines

Abstract: Wine quality is evaluated by sensory attributes and physicochemical properties whose relationship is intensely investigated. This work aimed to analyze the physicochemical properties and sensory attributes of wines from Bordô and Isabel American grapes elaborated by a traditional and two novel winemaking processes: pre-drying and submerged static pomace. It was possible to observe significant differences between the samples in all physicochemical properties (P \ 0.001), except in volatile acidity. Bordô and Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…For consumers, the ability to recognize aroma in wine can be influenced by several factors, the most important of which are emotional state, training and physiology (Castilhos et al, 2012). On a competitive consumer market, the concept of quality is entirely based on satisfying consumer expectations, and opposing expectations compromise product success in the consumer market (Castilhos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For consumers, the ability to recognize aroma in wine can be influenced by several factors, the most important of which are emotional state, training and physiology (Castilhos et al, 2012). On a competitive consumer market, the concept of quality is entirely based on satisfying consumer expectations, and opposing expectations compromise product success in the consumer market (Castilhos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On a competitive consumer market, the concept of quality is entirely based on satisfying consumer expectations, and opposing expectations compromise product success in the consumer market (Castilhos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific studies have shown that the habit of daily intake of red wine may be correlated to longevity, due to the presence of resveratrol that prevents the occurrence of cardiovascular diseases such as arteriosclerosis and thrombosis, controlling diabetes and reducing the risks of some cancers (GOLDFINGER, 2003). For these and other reasons, red wines from American cultivars are widely studied worldwide, especially regarding to sensory acceptance by consumers (CASTILHOS et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There have been some researches concerning the variations in winemaking processes which lead to ch a n ges i n sen sor y a t t r i but es a n d con sum er preferences (CHIRA et al, 2011;GREEN et al, 2011;CASTILHOS et al, 2012) and most of these studies evaluated consumer preference by the application of mul tivar iate stat istical t ools such as Princi pal Component Analysis and Cluster Analysis followed by Multidimensional Scaling. This statistical approach is taking its rightful place in the analysis of sensory results, because provide interesting findings that are not found in the univariate approach.…”
Section: Introductionmentioning
confidence: 99%